Physical Activity level and sedentary behavior of physical education students (Research, Society and Development, 2021)
The aim of the present study was to analyze the association between the level of physical activity and the sedentary behavior of Physical Education students at a college in the West Zone of the State of Rio de Janeiro. For this, a sample group of 90 students, 56 male and 34 females, was formed for convenience. All subjects answered the International Physical Activity Questionnaire and were categorized as satisfactorily active or unsatisfactorily active, as well as having their sitting time quantified representing sedentary behavior. To assess the association between the distributions, the Chi-Square test was applied and a significance level of 5% (p